Network and traffic engineering in emerging distributed computing applications - Abawajy, Jemal H.; Pathan, Mukaddim; Rahman, Mustafizur; Pathan, Al-Sakib Khan; Mat Deris, Mustafa (IGI Global, USA, 2013)
A distributed system consists of several autonomous computers that communicate through a computer network. Usually there is a common goal that all these networked computers try to achieve. The same definition could be rewritten by considering different types of computing devices instead of only computers in traditional sense. Examples of distributed computing systems include wireless sensor networks, Internet, World Wide Web (WWW), Peer-to-Peer (P2P) networks, multiplayer online games network and virtual reality network, distributed database network, distributed information processing network (e.g. airline ticket reservation system), aircraft control system, industrial control system, clustered and grid systems. As these technology paradigms are very diverse and vast, many types of network management issues are prevalent in present day Internet and distributed computing systems.